2012
DOI: 10.1371/journal.pone.0032474
|View full text |Cite
|
Sign up to set email alerts
|

First Efficacy Results of Capecitabine with Anthracycline- and Taxane-Based Adjuvant Therapy in High-Risk Early Breast Cancer: A Meta-Analysis

Abstract: BackgroundCapecitabine is effective and indicated for the salvage treatment of metastatic breast cancer. Therefore, it is essential to evaluate the efficacy of capecitabine in the adjuvant setting. There have been two large randomized studies to determine whether patients with high-risk early breast cancer benefit from the addition of capecitabine to standard chemotherapy, but they have yielded inconsistent results. We first undertook a meta-analysis to evaluate the efficacy of the addition of capecitabine ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 22 publications
2
11
1
1
Order By: Relevance
“…Another study showed an increased OS but not DFS (O'Shaughnessy et al 2009 ). A recent meta-analysis suggested an increased 5-year DFS and OS with adjuvant capecitabine (Jiang et al 2012 ). In our study, capecitabine significantly improved the 4-year DFS (p = 0.016), but the OS just failed to reach significance (p = 0.056), probably due to the small number of deaths.…”
Section: Discussionmentioning
confidence: 99%
“…Another study showed an increased OS but not DFS (O'Shaughnessy et al 2009 ). A recent meta-analysis suggested an increased 5-year DFS and OS with adjuvant capecitabine (Jiang et al 2012 ). In our study, capecitabine significantly improved the 4-year DFS (p = 0.016), but the OS just failed to reach significance (p = 0.056), probably due to the small number of deaths.…”
Section: Discussionmentioning
confidence: 99%
“…type="uri">www.ClinicalTrials.gov]. In the U.S. Oncology Group randomized trial USON01062, where 2611 women were assigned to receive first four cycles of doxorubicin and cyclophosphamide (AC) followed by either four cycles of docetaxel or four cycles of TX, there was no significant difference in the primary endpoint (disease-free survival) between the two arms, but women treated with TX had significantly better overall survival [16]. A joint analysis of the FinXX and the USON01062 trials found addition of capecitabine to a taxane-anthracycline regimen to improve significantly disease-free survival, overall survival and to reduce death from breast cancer [17], whereas a randomized single-center trial that compared weekly paclitaxel with TX as adjuvant or neo-adjuvant treatments of early breast cancer was interrupted early due to absence of benefit associated with TX [18]. …”
Section: Discussionmentioning
confidence: 99%
“…However, there is little evidence to support its effectiveness. A meta-analysis by Jiang et al demonstrated that disease-free survival significantly improved following addition of capecitabine to an anthracycline-taxane-based adjuvant chemotherapy in patients with high-risk early breast cancer (19). The final results of the FinXX trial indicated that the addition of capecitabine significantly improved breast cancer-specific survival, although not the recurrence-free survival, in early breast cancer (20).…”
Section: Discussionmentioning
confidence: 99%